2018
DOI: 10.1096/fj.201801402r
|View full text |Cite
|
Sign up to set email alerts
|

Slow‐twitch skeletal muscle defects accompany cardiac dysfunction in transgenic mice with a mutation in the myosin regulatory light chain

Abstract: Myosin light chain 2 (MYL2) gene encodes the myosin regulatory light chain (RLC) simultaneously in heart ventricles and in slow‐twitch skeletal muscle. Using transgenic mice with cardiac‐specific expression of the human R58Q‐RLC mutant, we sought to determine whether the hypertrophic cardiomyopathy phenotype observed in papillary muscles (PMs) of R58Q mice is also manifested in slow‐twitch soleus (SOL) muscles. Skinned SOL muscles and ventricular PMs of R58Q animals exhibited lower contractile force that was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…This coincided a decreased proportion of fiber type I/type II only in SOL muscles but not in the extensor digitorum longus muscles, as well as in differential regulation of proteins between the heart and SOL muscles of R58Q mice. These data suggest that MYL2 models of HCM may be used as a model to study the molecular, structural, and energetic mechanisms of RLC mutation-induced cardioskeletal myopathy 61 . Huang et al described a novel Asp94Ala (D94A) DCM mutation in MYL2 (Fig.…”
Section: Caleshu Et Al Discovered Another Point Mutation Gly57glu (mentioning
confidence: 86%
See 1 more Smart Citation
“…This coincided a decreased proportion of fiber type I/type II only in SOL muscles but not in the extensor digitorum longus muscles, as well as in differential regulation of proteins between the heart and SOL muscles of R58Q mice. These data suggest that MYL2 models of HCM may be used as a model to study the molecular, structural, and energetic mechanisms of RLC mutation-induced cardioskeletal myopathy 61 . Huang et al described a novel Asp94Ala (D94A) DCM mutation in MYL2 (Fig.…”
Section: Caleshu Et Al Discovered Another Point Mutation Gly57glu (mentioning
confidence: 86%
“…The study concluded that S15D-phosphomimic can be used as a potential rescue strategy to abrogate/alleviate the RLC mutation-induced phenotypes 131 . Interestingly, it was recently shown that R58Q-mutant mice showed functional similarities between the cardiac papillary muscles and slow-twitch soleus skeletal muscle, as evident by lower contractile force in both papillary and soleus muscles compared to fast-twitch extensor digitorum longus muscles of R58Q vs. wild-type-RLC mice 61 . This coincided a decreased proportion of fiber type I/type II only in SOL muscles but not in the extensor digitorum longus muscles, as well as in differential regulation of proteins between the heart and SOL muscles of R58Q mice.…”
Section: Caleshu Et Al Discovered Another Point Mutation Gly57glu (mentioning
confidence: 99%
“…Other important functions of myosin II are attributed to the RLC such as, folding to the 10S conformation (Trybus & Lowey, ), stiffness of the lever arm (Matthew, Khromov, Trybus, Somlyo, & Somlyo, ), coupling of ATPase and motility (Trybus, Waller, & Chatman, ), and intermolecular interactions in the dephosphorylated state (Liu, Shu, Hong, Levine, & Korn, ; Ni et al, ; Wendt, Taylor, Trybus, & Taylor, ). It is therefore not surprising that modifications throughout the RLC sequence can affect myosin function in general (Ikebe et al, ; Ikebe, Reardon, Mitsui, & Ikebe, ; Kambara et al, ; Kazmierczak et al, ; Ni et al, ; Ni et al, ; Rowe & Kendrick‐Jones, ; Rowe & Kendrick‐Jones, ; Sweeney, Yang, Zhi, Stull, & Trybus, ; Szczesna et al, ; Trybus & Chatman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Shu, Hong, Levine, & Korn, 2006;Ni et al, 2012;Wendt, Taylor, Trybus, & Taylor, 2001). It is therefore not surprising that modifications throughout the RLC sequence can affect myosin function in general (Ikebe et al, 1994;Ikebe, Reardon, Mitsui, & Ikebe, 1999;Kambara et al, 1999;Kazmierczak et al, 2019;Ni et al, 2009;Ni et al, 2012;Rowe & Kendrick-Jones, 1992;Rowe & Kendrick-Jones, 1993;Sweeney, Yang, Zhi, Stull, & Trybus, 1994;Szczesna et al, 2001;Trybus & Chatman, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation